Patologia e terapia dos edifícios do tribunal de justiça do Estado de Minas Gerais - Jose Agostinho de Hipona Rodarte Assuncao (2005)
This work emphasizes the typical formations of cracking, usually found at the buildings of the Court House of the State of Minas Gerais, starting from the causes of overload, excessive deformation and differential settlement of foundations; subjects mentioned in chapters 3, 4 and 5 respectively. In this work, there is no intention to give emphasis intheoretical or experimental formulations in order to calculate values for deformations or to obtain dimensions of openings of cracks, but to recognize the quality of these phenomenons, especially the behavior of these reinforced concrete structures while in service along the time. Chapters 1 and 2 are introductory and in chapter 6, deformationtopics, cracking, norm and mansonry are approached. Finally, in chapter 7 the study of cases is presented focusing these subjects with a critical analysis of six cases, in order to check if the interventions were technically and economically successful or not.